2010
DOI: 10.1027/1614-0001/a000011
|View full text |Cite
|
Sign up to set email alerts
|

Map Understanding as a Developmental Marker in Childhood

Abstract: A new test on map understanding for preschool and elementary-school children was constructed based on a Piagetian framework of the development of spatial ability and representational understanding. Results from a study with 95 3- to 6-year-old children are reported. The developmental trajectories for the performance components confirmed the construction rules and were explainable by Piagetian developmental stages.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 6 publications
0
12
0
Order By: Relevance
“…Children were more successful in trial which are required understanding spatial relations compared to the trial which are required mental rotation. Findings of the previous study with 95 3-to 6-year-old children (Peter, Glück and Beiglböck, 2010) showed that the majority of 6-year-olds use of spatial relations whereas mental rotation of maps was shown only by two 5-years old children. Spelke, Gilmore and McCarthy (2011) asked children aged 5-6 years to use a map of a particular geometric arrangement to place an object on a location indicated on the map.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Children were more successful in trial which are required understanding spatial relations compared to the trial which are required mental rotation. Findings of the previous study with 95 3-to 6-year-old children (Peter, Glück and Beiglböck, 2010) showed that the majority of 6-year-olds use of spatial relations whereas mental rotation of maps was shown only by two 5-years old children. Spelke, Gilmore and McCarthy (2011) asked children aged 5-6 years to use a map of a particular geometric arrangement to place an object on a location indicated on the map.…”
Section: Discussionmentioning
confidence: 79%
“…In addition, they should also recognize that these tools (like maps) are small-scale representation of larger spaces (Newcombe and Learmonth, 2005). Map understanding comprises three components: the first one is symbolic representations, the second is use of spatial relations and the third is mental rotation (Peter, Glück and Beiglböck, 2010). The first studies related to children"s map skills can be traced to Piaget and Inhelder.…”
mentioning
confidence: 99%
“…In order to assess the students' mental rotation ability, an adapted instrument of the Map Test for Children (Peter, Glück, & Beiglböck, 2010) was used. This instrument is designed for pre-and elementary school students to evaluate basic components of the use of maps.…”
Section: Instrumentsmentioning
confidence: 99%
“…Spatial concepts are some kind of implicit knowledge; their development is difficult to investigate (Peter, Glück, & Beiglböck, 2010). Spatial information concerns shapes, locations, paths, relations among entities and relations between entities and frames of reference (Newcombe & Shipley, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Spatial skills involve the ability to think and reason through comparison, manipulation, and transformation of the mental pictures (Casey et al, 2008). Understanding the maps offers one possibility of investigating children's understanding of spatial relations; and comprises three components that can be assessed in an independent way for understanding symbolic representations, use of spatial relations and mental rotation (Peter, Glück, & Beiglböck, 2010).…”
Section: Introductionmentioning
confidence: 99%